Inhibition of biological effects of endotoxins by phenothiazines - Molnár József (IN VIVO, 1992)
The importance of change transfer reaction involving endotoxins of bacteria and interactions between endotoxin-induced tumor necrosis factor (TNF) were investigated both in vitro and in vivo in the presence of several phenothiazines. Complex formation between endotoxins and ring-substituted phenothiazines, benzodiazepines, amantadine and promethazine was measured using spectrophotometric methods. The endotoxin-induced hypotensive effect was prevented by phenothiazine pretreatment of the dogs; however, the endotoxin-phenothiazine complex had the same effects as the endotoxin itself. The tumor necrosis factor-inducing ability of endotoxin in human monocytes was prevented by promethazine. The TNF induction by endotoxin was inhibited by promethazine in vivo.